AAV9-mediated gene delivery to liver grafts during static cold storage in a rat liver transplant model - Gao, Qimeng; Kesseli, Samuel J.; Gonzalez, Trevor; Zhang, Min; Kahan, Riley; Krischak, Madison; Halpern, Samantha E.; Song, Mingqing; Xu, Hongzhi; Abraham, Nader; Anwar, Imran J.; Alderete, Isaac; et al. (Frontiers in Transplantation, 2023)
Recombinant adeno-associated virus (rAAV) is a novel strategy used clinically for gene delivery, but has not been characterized in the context of organ transplantation. We sought to determine the efficacy of rAAV-mediated gene delivery during static cold storage (SCS) prior to liver transplantation. A triple-plasmid transfection protocol was used to produce rAAV subtype-9 vectors containing firefly luciferase genomes in HEK293 cells. Lewis rat liver grafts were flushed and stored in cold HTK solution. Three experimental groups received rAAV at different doses, administered via the portal vein as a bolus during SCS. A control group did not receive rAAV (N=2). Recipients then underwent syngeneic liver transplantation. Bioluminescence imaging to quantify in vivo luciferase expression was performed on post-operative days 7, 14, 28, and 56. Control animals demonstrated no bioluminescent activity, while animals receiving rAAV-treated livers had increasing bioluminescence, peaking at four weeks but sustained to the eight-week endpoint. This result was confirmed by experimental endpoint tissue luciferase activity assay. In conclusion, rAAV mediates gene transduction in liver grafts when administered during SCS and has potential for gene therapy applications in solid organ transplantation.